Environmental-Economic Heterocyclic Compound Synthesis: Synthesis and Characterization of Heterocyclic Compounds with Antibacterial Properties (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Heterocyclic compounds are the most diverse family of organic molecules. Due to extensivesynthetic research and their use in synthetic processes, the prevalence of heterocyclic compounds isgrowing. In medical chemistry and biochemistry, heterocyclic molecules are used. Recent plantproducedor discovered heterocyclic compounds with anti-fungal, anti-inflammatory, anti-bacterial,antioxidant, anti-convulsant, anti-allergic, herbicidal, and anti-cancer properties are the focus of thisresearch. The primary objective of this research is to synthesis heterocyclic molecules havingantibacterial characteristics. The findings suggested that the compound's antibacterial capabilities weremore potent, but its antifungal characteristics were less species-specific. In addition, the MBC resultswere obtained with Gentamycin